A comparison between symmetric and asymmetric key encryption algorithm based decryption mixnets - Ahmad, Sahan; Alam, Kazi Md Rokibul; Rahman, Habibur; Tamura, Shinsuke (2015 International Conference on Networking Systems and Security (NSysS), 2015)
This paper presents a comparison between symmetric and asymmetric key encryption algorithm based decryption mixnets through simulation. Mix-servers involved in a decryption mixnet receive independently and repeatedly encrypted messages as their input, then successively decrypt and shuffle them to generate a new altered output from which finally the messages are regained. Thus mixnets confirm unlinkability and anonymity between senders and the receiver of messages. Both symmetric (e.g. onetime pad, AES) and asymmetric (e.g. RSA and ElGamal cryptosystems) key encryption algorithms can be exploited to accomplish decryption mixnets. This paper evaluates both symmetric (e.g. ESEBM: enhanced symmetric key encryption based mixnet) and asymmetric (e.g. RSA and ElGamal based) key encryption algorithm based decryption mixnets. Here they are evaluated based on several criteria such as: the number of messages traversing through the mixnet, the number of mix-servers involved in the mixnet and the key length of the underlying cryptosystem. Finally mixnets are compared on the basis of the computation time requirement for the above mentioned criteria while sending messages anonymously.